Redesign Of The Panji Bako Sidikalang Stadium With An Approach To Contemporary Architectural Themes - Andalucia, Andalucia; Banjarnahor , Riski Bernados (Komunitas Menulis dan Meneliti (Kolibi), 2024)
In general, a stadium is a vital facility in soccer, serving as both a venue for matches and an entertainment hub for fans. The facilities and suitability of the stadium are crucial in attracting spectators, ensuring comfort, and providing an unforgettable experience. With comprehensive facilities and good management, a stadium can become a unique attraction. However, the Panji Bako Stadium in Sidikalang faces serious issues, namely inadequate facilities and low suitability levels, leading to a decline in spectator interest. Therefore, a comprehensive redesign is needed for this stadium. This redesign is expected to offer innovative and relevant solutions in accordance with contemporary demands, infusing a fresh and invigorating atmosphere into the long-standing stadium. The design process should consider various aspects, including enhancing facilities such as comfortable seating, commercial areas, and other supporting amenities. Moreover, sustainability aspects should ideally be integrated into the design, ensuring the stadium operates efficiently in terms of energy and environmental impact. Thus, the redesign will not only address existing problems but also open new opportunities for the development of soccer and entertainment in the area. Optimizing the stadium's function is expected to make it a proud icon that meets the expectations of players, fans, and the community.